EnaR: An r package for Ecosystem Network Analysis. Issue 11 (28th October 2014) - Borrett, Stuart R.; Lau, Matthew K.; Dray, Stephane
Summary Network analysis is a useful approach for investigating complex and relational data in many fields including ecology, molecular and evolutionary biology. Here, we introduce enaR, an r package for Ecosystem Network Analysis (ENA). ENA is an analytical tool set rooted in ecosystem ecology with over 30 years of development that examines the structure and dynamics of matter and energy movement between discrete ecological compartments (e.g. a food web). In addition to describing the primary functionality of the package, we highlight several features including a library of 100 empirical ecosystem models, the ability to analyse and compare multiple models simultaneously, and connections to other ecological network analysis tools in r.